PEMAHAMAN HIDUP DIPIMPIN OLEH ROH TERHADAP IMPLEMENTASI HIDUP DALAM BUAH ROH GALATIA 5:22-25 - sartin kela; Ragil Kristiawan; Gidion Gidion (STT Kristus Alfa Omega, 2022)
To be led by the Spirit means to be regulated to live in harmony with God. When a believer lives a life that tends to be led by the Spirit and obeys God, it can be manifested in the fruit of the Spirit that is produced. So, the purpose of this study is to find out whether there is a positive influence between the understanding of life being led by the Spirit on the implementation of life in the fruit of the Spirit Galatians 5:22-25 students of class 28 and 29 at the Alfa Omega Christ Theological College Semarang. Then it was found that the understanding of life being led by the Spirit contributed to the implementation of life in the fruit of the Spirit by 80.8% or included in the very strong category